Meningkatkan Kemampuan Speaking dan Writing Bahasa Inggris Melalui Kompetisi Spelling Bee - Shally Amna; Wienda Gusta; Yeng Primawati (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2021)
Abstract: Spelling Bee is a word spelling game which assessed the accuracy of words and the pronunciation of the letters in English. MTSN 7 Bungus, Padang was chosen as PKM partners due to the students’ low English language skills and interest. Therefore, through the Spelling Bee competition, the team tried to improve the students’ skills and interest in learning English language, especially their ability to write and spell words correctly. In this competition, there were 280 students previously trained before join the competition. This competition is divided into three rounds, namely the preliminary round, the semi-final round and the final round.  In addition, the English teachers also helped to coordinate the competition. During the activity, students were also given lessons on writing and spelling correctly. As a result, students’ enthusiasm in participating in competition can be one of the factors that triggers the enthusiasm and interests in learning so that they get more satisfying learning outcomes. During the competition, students were guided by the English teachers and given clear instructions. After participating in Spelling Bee competition, the students were not only given rewards but also some improvement in their English writing and spelling skills.Key Words: Spelling Bee, writing, spelling. Abstrak : Spelling Bee merupakan permainan mengeja kata dengan menilai keakuratan kata dan ketepatan pengucapan huruf yang disebutkan dalam Bahasa Inggris. MTSN 7 Bungus, Padang dipilih sebagai mitra PKM karena kemampuan dan minat Bahasa Inggris siswanya yang sangat rendah. Oleh karena itu, lewat kompetisi Spelling Bee, Tim PKM berusaha untuk meningkatkan kemampuan dan minat siswa terhadap Bahasa Inggris terutama pada kemampuan menulis dan mengeja kata. Dalam Kegiatan Spelling Bee ini, sebanyak 280 siswa dilatih sebelum mengikuti kompetisi Spelling Bee yang terbagi atas tiga babak, yaitu preliminary Round, Semi Final Round dan yang terakhir Final round. Selain itu, guru Bahasa Inggris di sekolah tersebut turut membantu demi kelancaran kegiatan kompetisi ini. Siswa diberikan pelajaran tentang menulis dan mengeja bahasa Inggris dengan benar. Antusias siswa dalam mengikuti kompetisi dapat merupakan salah satu faktor yang memicu semangat dan daya tarik siswa dalam belajar sehingga memperoleh hasil belajar yang jauh lebih memuaskan. Selama kompetisi, siswa dipandu oleh guru bahasa Inggrisnya dan diberikan instruksi yang jelas. Setelah mengikuti kompetisi Spelling Bee ini, siswa siswi MTSN 7 Bungus tidak hanya diberikan reward namun juga dapat meningkatkan kemampuan menulis dan mengeja Bahasa Inggrisnya.Kata Kunci: spelling bee; writing; spelling.